Modernization in Asia: the environment/resources, social mobilization, and traditional landscapes across time and space in Asia - Abe, Satoshi; Lim, Tai Wei (World Scientific, 2022)
"This book explores the unfolding of modernity in the greater Asia that uniquely takes shape at different times and places, with a particular attention to a common thread that has been at heart of the development: religion. The status of religion has been relegated in the Western modernity to such that its effects be restricted within the private realm and not be exerted in the public or one's rationality. This edited volume sheds light on the multifarious forces of religion both in the past and present that have impacted on the essential aspects of modern society - aspects in which one does not usually have recourse to religion in the West - from science and technology, politics, and to identity in Asia. Interdisciplinary approaches in the volume allow one to broadly examine religious practices within Asian contexts, thus enabling to reevaluate the concept, scope, and gamut of so-called religion"--